2008
DOI: 10.1080/17518420701419227
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of learning difficulties in children after treatment for a cerebellar medulloblastoma: A single-case study

Abstract: In the process of establishing a methodology for individualized remediation programmes in children treated for cerebellar tumour, this study followed prospectively over 11 years a young child treated for a medulloblastoma at 18 months of age throughout the rehabilitation process. Repeated neuropsychological and academic evaluations evidenced temporary disruptive behaviour, deficient manual and visual abilities, attention and working memory difficulties, but preserved language abilities, in relation with vermia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
0
10
0
1
Order By: Relevance
“…61 Butler and Cope land found that childhood cancer survivors who participated in cognitive training improved significantly in all attentional measures. In another study by Callu et al, 9 rehabilitation allowed a child treated for a medulloblastoma to have fluent progression at school. The program encourages various groups, including the rehabilitation team, psychotherapists, parents, and teachers, to work together to improve cognitive function for these children.…”
Section: Remediation In Childhood Cancer Survivorsmentioning
confidence: 99%
“…61 Butler and Cope land found that childhood cancer survivors who participated in cognitive training improved significantly in all attentional measures. In another study by Callu et al, 9 rehabilitation allowed a child treated for a medulloblastoma to have fluent progression at school. The program encourages various groups, including the rehabilitation team, psychotherapists, parents, and teachers, to work together to improve cognitive function for these children.…”
Section: Remediation In Childhood Cancer Survivorsmentioning
confidence: 99%
“…The results of the outreach programme dedicated specifically to the children in the cancer centre have been published recently and indicate that it is crucial to co‐ordinate the complex rehabilitation and academic achievement of those children over the long‐term and that a programme such as this is very beneficial (Kieffer et al . 2007; Callu et al . 2008).…”
Section: Resultsmentioning
confidence: 99%
“…There is also an impairment of fine motor skills, as for adult patients with cerebellar damage (Ribi et al, 2005). Children with lesions of the cerebellum obtain low scores in the Purdue Pegboard test (PP) (Tiffin, 1948) used to assess manual dexterity (Callu et al, 2008;Grill et al, 2004;Puget et al, 2009). Recently, Puget et al (2009) showed that the degree of dysfunction in coordination of fine movements measured by the PP test was directly correlated to the extent of injury to both dentate nuclei and inferior vermis, irrespective of other risk factors such as the age at diagnosis or the interval since radiotherapy.…”
Section: Introductionmentioning
confidence: 99%